Flexible Transparent Barrier Applications of Oxide Thin Films Prepared by Photochemical Conversion at Low Temperature and Ambient Pressure - With, Patrick C.; Helmstedt, Ulrike; Prager, Lutz (Frontiers in Materials, 2020)
Photoconversion of metal-organic precursors to thin film metal oxides using ultraviolet (UV) radiation in oxidative atmosphere is an attractive technology because it can be applied at temperatures < 80 °C and at ambient pressure. Thus, it enables preparing this class of thin films in a cost-efficient manner on temperature sensitive substrates such as polymer films. In this article, various aspects of research and development in the field of photochemical thin-film fabrication, with particular focus to the application of the produced films as gas permeation barriers for the encapsulation of optoelectronic devices are reviewed. Thereby, it covers investigations on fundamental photochemically initiated reactions for precursor classes containing metal-oxygen and metal-nitrogen bonds, and emphazises the relevance of that understanding for applicative considerations like integration of the single-layer barrier films into relevant encapsulation films. Further perspectives are given concerning integration of additional functionalities like electrical conductivity to the flexible and transparent barrier films.